2010
DOI: 10.1158/1078-0432.ccr-10-1105
|View full text |Cite
|
Sign up to set email alerts
|

Portable Filter-Based Microdevice for Detection and Characterization of Circulating Tumor Cells

Abstract: Purpose: Sensitive detection and characterization of circulating tumor cells (CTC) could revolutionize the approach to patients with early-stage and metastatic cancer. The current methodologies have significant limitations, including limited capture efficiency and ability to characterize captured cells. Here, we report the development of a novel parylene membrane filter-based portable microdevice for size-based isolation with high recovery rate and direct on-chip characterization of captured CTC from human per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
387
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(395 citation statements)
references
References 17 publications
6
387
0
2
Order By: Relevance
“…Furthermore, the randomly distributed holes are prone to significant coalescence of two or more holes allowing tumor cells to escape from the filter. More recent studies have shown that a variety of microfabrication techniques could be used to manufacture filters of different hole-types and densities [36][37][38][39][40][41][42][43][44][45] , but none of them were able to meet the critical requirements for both clinical application and fundamental studies. …”
mentioning
confidence: 99%
“…Furthermore, the randomly distributed holes are prone to significant coalescence of two or more holes allowing tumor cells to escape from the filter. More recent studies have shown that a variety of microfabrication techniques could be used to manufacture filters of different hole-types and densities [36][37][38][39][40][41][42][43][44][45] , but none of them were able to meet the critical requirements for both clinical application and fundamental studies. …”
mentioning
confidence: 99%
“…Thus, different devices based on cell filtration and centrifugal force have been recently developed. [9][10][11] Membrane-based filter systems, such as isolation by size of epithelial tumor cells (ISET), have demonstrated to be an efficient, inexpensive, and quick method for enriching CTCs. 12 A direct comparison of CellSearch and ISET for CTCs isolation demonstrated that ISET performed better than CellSearch in detecting CTCs in patients with metastatic prostate carcinoma and metastatic lung carcinoma.…”
Section: Detection and Enrichment Techniquesmentioning
confidence: 99%
“…2 Furthermore, circulating pancreatic cells exist in a subset of patients without cancer but with potentially cancerous pancreatic cystic lesions. 4 To obtain this information, CTCs have been successfully captured from blood samples through mechanical, 7 electromechanical 8 and immunoaffinity methods, 9-11 the last being the most common. However, challenges exist capturing subsets of CTCs that have reduced antigen expression, often associated with the epithelial to mesenchymal transition (EMT) 12 or acquired resistance to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%